Environmental Influences on the Drying Rate of Spray-Applied Disinfestants from Horticultural Production Surfaces - Warren E. Copes; Quentin Read; Barbara J. Smith (PhytoFrontiers)
Drying rates of disinfestants commonly applied to horticultural plant production surfaces were evaluated under cool to hot weather and under laboratory conditions to characterize the range of drying times and how this relates to contact times specified on product labels. Drying rates of six disinfestants (isopropyl alcohol [IPA], two quaternary ammonium compounds [QACs], two peroxygen compounds [PXs], and sodium hypochlorite [bleach]) and water were evaluated when applied to six substrate materials (concrete, galvanized metal, polypropylene ground fabric, polyethylene plastic sheet, pressure-treated pine, and twin-wall clear polycarbonate) based on the weather variables of solar radiation, temperature, and relative humidity. Differences were evident at the point of application. Disinfestants with low (IPA, both QACs, and one PX) and high (bleach, one PX, and water) surface tension provided approximately 100 and 60% coverage, respectively, when applied to horizontal, nonporous solid materials. Disinfestants applied to horizontal porous materials (concrete, fabric, and wood) persisted on the surface for a mean of only 9 to 113 s because solutions were actively drawn into the substrates’ internal structure. Disinfestants applied to vertical twin-wall greenhouse material flowed off, while retaining only a maximum beaded wetness coverage of 14%. A Bayesian analysis procedure was used to model drying effects of disinfestants correlated with substrate and weather variables based on posterior marginal and prediction trends. Generally, the fastest drying rate occurred in the first 2.5 min, and approximately 50% of coverage was retained by 5 min. The evaporative process was variable with distinct interactions occurring among the experimental variables. [Figure: see text] The author(s) have dedicated the work to the public domain under the Creative Commons CC0 “No Rights Reserved” license by waiving all of his or her rights to the work worldwide under copyright law, including all related and neighboring rights, to the extent allowed by law, 2024.